A Randomized Study of Allopurinol on Endothelial Function and Estimated Glomular Filtration Rate in Asymptomatic Hyperuricemic Subjects with Normal Renal Function - Kanbay, Mehmet; Huddam, Bulent; Azak, Alper; Solak, Yalcin; Kadioglu, Gulay Kocak; Kirbas, Ismail; Duranay, Murat; Covic, Adrian; Johnson, Richard J. (Clinical journal of the American Society of Nephrology, 2011)
Endothelial dysfunction is an early manifestation of vascular injury and contributes to the development of atherosclerotic cardiovascular disease. Recent studies have implicated hyperuricemia as a risk factor for cardiovascular disease. We hypothesized that lowering uric acid in subjects with asymptomatic hyperuricemia with allopurinol might improve endothelial dysfunction, BP, estimated GFR (eGFR), and inflammatory markers. Subjects with asymptomatic hyperuricemia and no history of gout and 30 normouricemic control subjects were enrolled in this 4-month randomized prospective study. Thirty hyperuricemic patients received 300 mg/d allopurinol and were compared with 37 hyperuricemic patients and 30 normouricemic subjects in matched control groups. Flow-mediated dilation (FMD), eGFR, ambulatory BP monitoring, spot urine protein-creatine ratio, and highly sensitive C-reactive protein were measured at baseline and at 4 months. Age, gender, lipid profile, eGFR, hemoglobin, glucose, and level of proteinuria were similar in hyperuricemic subjects and controls at baseline. As expected, hyperuricemic patients had higher levels of highly sensitive C-reactive protein and lower FMD compared with normouricemic patients. Allopurinol treatment resulted in a decrease in serum uric acid, a decrease in systolic BP, an increase in FMD, and an increase in eGFR compared with baseline. No significant difference was observed in the control hyperuricemic and normouricemic groups. In a multiple regression analysis, FMD levels were independently related to uric acid both before (beta = -0.55) and after (beta = -0.40) treatment. Treatment of hyperuricemia with allopurinol improves endothelial dysfunction and eGFR in subjects with asymptomatic hyperuricemia.